Kinetic and Mechanistic Studies of the Interaction of DL-methionine with cis-diaqua(cis-1,2-diaminocyclohexane)Platinum(II)Perchlorate in Aqueous Medium at pH 4.0 - Mukhopadhyay Sudip Kumar (International Journal of Research in Chemistry and Environment (IJRCE), 2015)
The kinetics of the interaction of DL-methionine with cis-[Pt(dach)(H2O)2](ClO4)2 (dach=cis-diaminocyclohexane) have been studied spectrophotometrically as a function of [Pt(dach)(H2O)22+], [DL-met] and temperature at a particular pH (4.0). The reaction proceeds via rapid outer sphere association complex formation followed by two consecutive slower steps (k1 and k2 of the order of 10-3s-1 and 10-5s-1 respectively).The first step involves the transformation of outer sphere complex into an inner sphere complex containing Pt-S bond and one aqua ligand, while the second step involves chelation when second aqua ligand is replaced. The equilibrium constant has been evaluated. The activation parameters for both the steps have been calculated (ΔH1 # = 13.73 ± 2.09 kJ mol-1 ΔS1 # = -251.68 ± 6.76 J K-1mol-1ΔH2 # = 90.96 ± 1.26 kJ mol-1 ΔS2 # =- 40.99 ± 4.06 J K-1mol-1). The low enthalpy of activation and negative entropy of activation suggest associative interchange mechanism. Also, from the thermodynamic consideration, this type of formation of outer sphere association complex is supported by the negative ΔG0 (-16.60 kJ mol-1).